Innovations as key to the green revolution in Africa exploring the scientific facts - Bationo, Andre; Boaz. Waswa; Okeyo,Jeremiah M.; Maina Fredah; Kihara, Job Maguta (Springer, 2011)
Africa urgently needs a uniquely African Green Revolution- a revolution that is long overdue, a revolution that will help the continent in its quest for dignity and peace   Mr. Kofi Annan, Former Secretary General of the United Nations (UN), currently the Board Chair of Alliance for a Green Revolution in Africa (AGRA) Research work on soil in Sub-Saharan Africa (SSA) has generated numerous outputs but very few have been translated into adoption to improve the livelihoods of the smallholder farmers. This is the greatest challenge Africa needs to address in order to achieve the highly sought after green revolution Andre Bationo Soil Health Specialist, Alliance for a Green Revolution in Africa (AGRA), Accra, Ghana. An African Green Revolution can apply the power of knowledge and technology with an environmental touch: disseminating many crop varieties that will thrive in diverse conditions; improving soil health through integrated soil fertility management; and developing technologies that maximize the use of rainwater, deliver small-scale irrigation and mitigate against impacts of unfavourable and changing climatic conditions.